BS EN 61754-7-4 Ed.1.0. Fibre optic interconnecting devices and passive components. Fibre optic connector interfaces. Part 4. Systematic aspects for the application of reed switches in safety related parts of control systems (26th April 2021) - British Standards Institution,
No abstract available